An Analysis of Lexical and Syntactical Errors in English Abstract Made by Students of the Accounting Department Polmed - Nuraini Nuraini; Ridwan Hanafiah; Masdiana Lubis (LPPM Universitas Jambi, 2020)
The main purpose of the study is to find out the kinds of lexical and syntactical errors in writing the student’s paper of English Abstract. The data collecting technique used the field research method from 25 student’s papers of English abstract of Accounting Department Politeknik Negeri Medan. The method used in the research is a qualitative approach. The findings of the research revealed that there were so many errors found in the student’s papers of English abstract. There were two kinds of lexical errors relate to Semantic Error in Lexis found in the student’s papers of English abstract which are Confusion of Sense Relations and Collocational Errors. The number of errors in Confusion of Sense was 20 errors with percentage 62.50 % while the collocational errors were also found as many as 12 errors that constituted 37,50% of the total errors collected in the data analysis process. The errors in the syntactical level are also found in the student’s paper of English abstract based on surface structure taxonomy. There were five kinds of errors found in the analysis process. The most frequent errors made by students are misformation 62 (40,79%) of error followed by omission error reach 54 (35,53%) of errors. The addition errors reach 22 (14,47%) of error. then, misordering errors are found 13 (8,55%) of errors. finally, the blend is only found 1 (0,66%) of errors in student’s papers of English abstract in Accounting Department Politeknik Negeri Medan.